2018
DOI: 10.1186/s13071-018-3017-z
|View full text |Cite
|
Sign up to set email alerts
|

Hematobin is a novel immunomodulatory protein from the saliva of the horn fly Haematobia irritans that inhibits the inflammatory response in murine macrophages

Abstract: BackgroundThe horn fly Haematobia irritans is a blood-sucking ectoparasite responsible for substantial economic loss of livestock. Like other hematophagous arthropods species, the successful blood-feeding of H. irritans is highly dependent on the modulation of the host’s hemostasis and immune system. Here, we evaluated the biological activity of hematobin (HTB), a protein recently identified in the H. irritans saliva, on macrophage biology. The goal was to understand the putative interactions between the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Utilization of salivary fly protein has been studied in overcoming several pathological problems in experimental mammal individuals. The progress of such studies is in line with the report of Breijo et al (2018) indicated that proteins obtained from the substances of horn fly saliva (Haematobia irritans) were able to inhibit the inflammatory in an experiment using mice. The protein which is contained in the body of the Haematobia irritans insect functions as a molecule capable in controlling the insect infestation in livestock as traced by Breijo et al (2017).…”
Section: Resultssupporting
confidence: 62%
“…Utilization of salivary fly protein has been studied in overcoming several pathological problems in experimental mammal individuals. The progress of such studies is in line with the report of Breijo et al (2018) indicated that proteins obtained from the substances of horn fly saliva (Haematobia irritans) were able to inhibit the inflammatory in an experiment using mice. The protein which is contained in the body of the Haematobia irritans insect functions as a molecule capable in controlling the insect infestation in livestock as traced by Breijo et al (2017).…”
Section: Resultssupporting
confidence: 62%
“…In addition, the presence of syn-AeMOPE-1 in cultures of resting macrophage did not affect the basal levels of the parameters evaluated. Similarly, macrophage viability was monitored by flow cytometry and by a resazurin-based assay (21,34,44), and no evidence was found concerning AeMOPE-1 toxicity under these conditions. The literature on the activities of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were immunized with syn-AeMOPE-1 (20 µg/animal) emulsified in adjuvant as described ( 34 ). Two weeks after the last immunization, mice received an i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Concomitantly, 25 µl of 0.01% resazurin (prepared in complete medium) were added to all wells. Cell viability was evaluated after 48 h of culture by reading the culture absorbance at 570 and 600 nm in a plate reader and the results are expressed as the difference between those readings as described [20, 29, 30].…”
Section: Methodsmentioning
confidence: 99%